2014
DOI: 10.1016/j.contraception.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Does tenofovir gel or do other microbicide products affect detection of biomarkers of semen exposure in vitro?

Abstract: Objectives There is currently no information on whether products evaluated in HIV microbicide trials affect the detection of the semen biomarkers prostate-specific antigen (PSA) or Y chromosome DNA. Study Design We tested (in vitro) dilutions of tenofovir (TFV), UC781 and the hydroxyethylcellulose (HEC) placebo gels using the Abacus ABAcard and the quantitative (Abbott Architect total PSA) assays for PSA and Y chromosome DNA by real-time polymerase chain reaction. Results TFV gel and the HEC placebo advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…We were unable to confirm the absence of vaginal prostate-specific antigen with point-of-care testing for the TFV gel during visits because TFV gel may interact with the assay. 19 Laboratory staff evaluating end points viewed only the participant number and did not have access to participant age, cohort, visit type, or other identifying information. This article reports on data obtained from visits where TFV 1% gel was used (as above and bolded in Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…We were unable to confirm the absence of vaginal prostate-specific antigen with point-of-care testing for the TFV gel during visits because TFV gel may interact with the assay. 19 Laboratory staff evaluating end points viewed only the participant number and did not have access to participant age, cohort, visit type, or other identifying information. This article reports on data obtained from visits where TFV 1% gel was used (as above and bolded in Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Over the past few years, our laboratory has explored the in vitro effect of several different substances that may be used intravaginally and may affect some of the semen biomarker assays. Our experiments have demonstrated that some vaginal products (including microbicides) can affect the performance of some of the PSA 38-41 or Yc-DNA 40-41 assays. A summary of our results, which have been previously published, 38-41 is outlined in Table 1.…”
Section: Specific Considerations For the Semen Biomarker Assaysmentioning
confidence: 86%
“…For example, the microbicide product tenofovir did not interfere with the performance of the quantitative PSA assay (total PSA for the Abbott Architect system), but did interfere with the performance of the qualitative assay (ABAcard). 40-41 …”
Section: Specific Considerations For the Semen Biomarker Assaysmentioning
confidence: 99%
“…Vaginal douching, a highly prevalent feminine hygiene practice [15], is expected to accelerate the biomarkers’ clearance. In vitro assays have shown that some microbicides and lubricants could lead to partial or total inhibition of Yc-DNA detection [16, 17]. In observational settings where time since semen exposure and thus, biomarkers concentration, may vary, where condom breakage or slippage may lead to low exposure to semen, where menses or vaginal douching are expected to washout semen, and where women can use topical products that might interfere with biomarkers detection, an assay that allows the detection of low target concentrations is required.…”
Section: Introductionmentioning
confidence: 99%